Economic Cooperation and Confrontation between Europe and the USA. A Game Theoretic Approach to the Analysis of International Monetary and Trade Policies - Giorgio Basevi; Paolo Kind; Giorgio Poli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1986)
It has recently become common, and almost fashionable, to analyze problems of economic policy with the techniques of game theory.
Keywords: 330